High-brightness high-color-fastness fluorescent polyester fiber and preparation method thereof

CN122898981APending Publication Date: 2026-10-13POLY PLASTIC MASTERBATCH SUZHOU
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611300338.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

但该方法存在明显缺陷:荧光颜料与聚酯基材的相容性较差,在熔融过程中易团聚,导致纤维光泽不均匀;同时荧光颜料缺乏有效载体束缚,在后续洗涤、摩擦和光照过程中易脱落、降解,使得纤维色牢度不佳,严重影响产品使用寿命

Benefits of technology

(1)色牢度显著提升:二氧化硅对荧光颜料的吸附束缚作用,有效减少其在洗涤、摩擦过程中的脱落,耐洗色牢度达4~5级,耐光色牢度达4级,较直接熔融纺丝产品提升1~2级;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898981A_ABST
    Figure CN122898981A_ABST
Patent Text Reader

Abstract

The application discloses a kind of high-brightness high-color fastness fluorescent polyester fibers and preparation method, belong to functional polyester fiber technical field.The fiber is composed of polyester base material and silica-fluorescent pigment compound, wherein silica-fluorescent pigment compound accounts for 3%~8% of the total mass of fiber, the load of fluorescent pigment in compound is 15%~30% of the mass of silica, and the particle size of silica is 20~100nm.The application utilizes the high specific surface area adsorption characteristics of nanosilica, solves the problem of uneven dispersion and easy falling off of fluorescent pigments in traditional direct melt spinning, and the finished fiber has light fastness ≥4 levels and gloss ≥60%.Compared with the prior art, the color fastness is improved by 1~2 levels, the brightness is significantly optimized, and the application has good industrialization application prospect and is suitable for clothing, decoration, anti-counterfeiting and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional polyester fiber technology, specifically relating to a high-gloss, high-colorfastness fluorescent polyester fiber and its preparation method. Background Technology

[0002] Fluorescent polyester fibers are widely used in clothing, decoration, and anti-counterfeiting due to their vibrant visual effect. Currently, the preparation of fluorescent polyester fibers mostly employs the direct melt spinning method, which involves directly mixing fluorescent pigments with polyester chips and then melt spinning. However, this method has significant drawbacks: the compatibility between fluorescent pigments and the polyester substrate is poor, and they easily agglomerate during the melting process, resulting in uneven fiber gloss; simultaneously, the fluorescent pigments lack effective carrier binding, making them prone to detachment and degradation during subsequent washing, rubbing, and light exposure, leading to poor fiber color fastness and severely impacting product lifespan.

[0003] While existing technologies include methods for modifying polyester fibers with nanoparticles, such as adding nano-silica to polyester to improve UV resistance or mechanical strength, none address the design of utilizing silica's adsorption properties to load fluorescent pigments and improve colorfastness. The preparation of some fluorescent functional materials simply involves mixing silica with fluorescent masterbatches without forming a stable adsorption complex, thus failing to solve the core problems of uneven pigment dispersion and insufficient colorfastness. Therefore, developing a polyester fiber preparation technology that can achieve stable loading of fluorescent pigments while simultaneously providing high gloss and high colorfastness has become an urgent need for the industry. Summary of the Invention

[0004] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.

[0005] In view of the problems existing in the above and / or prior art, the present invention is proposed.

[0006] Therefore, the purpose of this invention is to overcome the shortcomings of the prior art and provide a high-gloss, high-colorfastness fluorescent polyester fiber.

[0007] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a high-gloss, high-colorfastness fluorescent polyester fiber, characterized in that it is composed of a polyester substrate and a silica-fluorescent pigment composite; the silica-fluorescent pigment composite accounts for 3% to 8% of the total fiber mass, and the remainder is the polyester substrate; in the silica-fluorescent pigment composite, the fluorescent pigment loading is 15% to 30% of the silica mass, and the silica particle size is 20 to 100 nm.

[0008] As a preferred embodiment of the high-gloss, high-colorfastness fluorescent polyester fiber of the present invention, wherein: the lightfastness of the fiber is ≥4 and the gloss is ≥60%.

[0009] As a preferred embodiment of the high-gloss, high-colorfastness fluorescent polyester fiber of the present invention, wherein: the fluorescent pigment is at least one of rare earth fluorescent powder, fluorescent pigment, and fluorescent dye, and the particle size of the fluorescent pigment is <5μm.

[0010] As a preferred embodiment of the high-gloss, high-colorfastness fluorescent polyester fiber of the present invention, the polyester substrate is polyethylene terephthalate (PET) or polybutylene terephthalate (PBT), with an intrinsic viscosity of 0.65~0.85 dL / g.

[0011] Another object of the present invention is to overcome the shortcomings of the prior art and provide a method for producing high-gloss, high-colorfastness fluorescent polyester fibers, characterized by comprising, Nano-silica was mixed with fluorescent pigment and stirred in an aqueous solution at 60-80℃ for 2-4 hours for adsorption. After centrifugation and vacuum drying at 80-100℃, a silica-fluorescent pigment composite was obtained. The silica-fluorescent pigment composite was mixed with polyester chip powder and an antioxidant was added. The mixture was stirred at 400-1000 r / min for 10-20 min, and then melt-extruded, granulated, and dried to obtain the masterbatch. The obtained masterbatch is mixed with polyester chips, melted, filtered and extruded through a spinneret, then cooled, oiled, wound and stretched to obtain the fluorescent polyester fiber.

[0012] In a preferred embodiment of the preparation method described in this invention, the mass ratio of the nano-silica to the fluorescent pigment is 3.3~6.7:1.

[0013] As a preferred embodiment of the preparation method described in this invention, the contents of the silica-fluorescent pigment composite, polyester chip powder, and antioxidant are 5%~12%, 88%~95%, and 0.1%~0.3% respectively, based on the mass percentage of the masterbatch raw materials.

[0014] In a preferred embodiment of the preparation method described in this invention, the mass ratio of the masterbatch to the polyester chips is 10~20:80~90.

[0015] As a preferred embodiment of the preparation method described in this invention, the masterbatch is obtained after melt extrusion granulation and drying, wherein the extrusion temperature is 230~280℃, the screw speed is 200~300r / min, the barrel temperature gradient is 230℃~250℃~260℃~280℃, the drying temperature is 80~120℃, and the drying time is 4~6h.

[0016] As a preferred embodiment of the preparation method described in this invention, the fluorescent polyester fiber is obtained by: melting, filtering, extruding through a spinneret, followed by cooling, oiling, winding, and stretching. The spinneret has a spinneret orifice diameter of 0.2~0.5mm and a number of orifices of 36~72; the oiling rate is controlled at 0.5%~0.8%, and the extrusion temperature is 255~290℃; cooling is achieved by cooling the melt stream through a ring-blown air system at a speed of 0.5~1.2m / s and a temperature of 20~25℃; the winding speed is 1500~2000m / min; the stretching ratio is 2.5~3.2, and the setting temperature is 110~130℃.

[0017] Beneficial effects of this invention: (1) Significantly improved color fastness: The adsorption and binding effect of silica on fluorescent pigments effectively reduces their shedding during washing and rubbing. The wash fastness reaches level 4-5 and the light fastness reaches level 4, which is 1-2 levels higher than that of direct melt spinning products; (2) Stable and controllable process: The pigment dispersion is optimized through the masterbatch preparation process to avoid clogging of the spinneret during spinning, which is suitable for industrial production; (3) Strong compatibility; it can be adapted to a variety of polyester substrates such as PET and PBT, and has a wide range of fluorescent pigments to choose from, making it flexible in application scenarios. Attached Figure Description

[0018] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein: Figure 1 These are the performance test results of the fibers obtained in Examples 1-3 of this invention.

[0019] Figure 2 The results are the performance test results of the fibers obtained in Comparative Examples 1 to 3 of this invention.

[0020] Figure 3 The results are the performance test results of the fibers obtained in Comparative Examples 4-6 of this invention.

[0021] Figure 4 These are the performance test results of the fibers obtained in Examples 1-3 of this invention after aging.

[0022] Figure 5 These are the performance test results of the fibers obtained in Comparative Examples 1-3 of this invention after aging.

[0023] Figure 6These are the performance test results of the fibers obtained in Comparative Examples 4-6 of this invention after aging. Detailed Implementation

[0024] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.

[0025] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0026] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.

[0027] The instruments used in the embodiments of this invention are as follows: twin-screw extruder: Leistritz ZSE 40 CC, spinning test machine: Zibo Linzi Fangchen Masterbatch Factory FCF-5, texturing machine: Yuejian YJ80OM high-speed computer texturing machine, colorimeter: X-Rite, aging chamber: Q-LAB Q-SUN Xe-2HS (Xe-2 HS) air-cooled xenon lamp aging test chamber.

[0028] The fluorescent pigment selected in this embodiment of the invention is Aminoketone; the antioxidant can be selected from the range of 1010, 9228, and 1577.

[0029] In all embodiments of the present invention, PET chips are used as polyester substrate. In the embodiments of the present invention, the PET chips selected are Sanfangxiang PET bottle grade chips CZ318, and the chip powder is obtained by grinding PET chips to 0.1~0.2mm.

[0030] Example 1 This embodiment provides a method for preparing high-gloss, high-colorfastness fluorescent polyester fiber, specifically including the following steps: (1) Preparation of silica-fluorescent pigment composite: 80g of nano-silica (50nm particle size) and 20g of fluorescent yellow pigment (3um particle size) (20% loading) were added to 1000mL of deionized water, stirred and adsorbed at 70℃ for 3h, centrifuged at 6000r / min for 5min, and then vacuum dried at 90℃ for 5h to obtain silica-fluorescent pigment composite. (2) Masterbatch preparation: 50g of silica-fluorescent pigment composite was mixed with 948g of PET chip powder, and 2g of antioxidant 1010 was added. The mixture was stirred at 1200 r / min for 15 min, followed by melt extrusion granulation. The screw speed of the twin-screw extruder was 280 r / min, and the barrel temperature gradient was 230℃ / 250℃ / 260℃ / 280℃. After cooling, the mixture was granulated to obtain masterbatch particles with a diameter of 2.5±0.2mm and a length of 3.0±0.2mm. The masterbatch was then dried at 110℃ for 5 h. (3) Melt spinning: 150g of masterbatch was mixed with 850g of PET chips, melted, filtered, and then extruded through a spinneret. After cooling, oiling, winding, and stretching, fluorescent polyester fiber was obtained. The single-screw extrusion temperature was 290℃; the spinneret had 48 holes with a diameter of 0.3mm; the ring blower speed was 0.8 m / s and the temperature was 22℃; the oiling rate was 0.6%; the winding speed was 1800 m / min; the draw ratio was 2.8; and the setting temperature was 120℃.

[0031] Example 2 The difference between this embodiment and embodiment 1 is that the amount of antioxidant added in step (2) is replaced with 1%, and the remaining steps are the same as in embodiment 1, to obtain fluorescent polyester fiber.

[0032] Example 3 The difference between this embodiment and embodiment 1 is that the amount of antioxidant added in step (2) is replaced with 0%, and the remaining steps are the same as in embodiment 1, to obtain fluorescent polyester fiber.

[0033] Comparative Example 1 10g of fluorescent pigment (same type as in Example 1), 2g of antioxidant, and 988g of PET chip powder were directly mixed and melt-spun according to the spinning process parameters of Example 1 to obtain the comparative fiber.

[0034] Comparative Example 2 The difference between this comparative example and Example 1 is that the silica in step (1) is replaced with a particle size of 2.5 μm, while the rest of the steps are the same as in Example 1, to obtain fluorescent polyester fibers.

[0035] Comparative Example 3 The difference between this comparative example and Example 1 is that the silica in step (1) is replaced with particles with a diameter of 0.1 μm, while the rest of the steps are the same as in Example 1, resulting in fluorescent polyester fibers.

[0036] Comparative Example 4 The difference between this comparative example and Example 1 is that the silica adsorption in step (1) is replaced by direct physical mixing, while the remaining steps are the same as in Example 1, resulting in fluorescent polyester fibers.

[0037] Comparative Example 5 The difference between this comparative example and Example 1 is that the antioxidant in step (2) is replaced with 9228, while the rest of the steps are the same as in Example 1, resulting in fluorescent polyester fibers.

[0038] Comparative Example 6 The difference between this comparative example and Example 1 is that the antioxidant in step (2) is replaced with 168, while the rest of the steps are the same as in Example 1, resulting in fluorescent polyester fibers.

[0039] The x, y, and β values ​​of high-gloss, high-colorfastness fluorescent polyester fibers were tested according to EN ISO 20471:2013 "High-visibility clothing - Test methods and requirements". The test results are shown in Table 1. For detailed results, please refer to... Figures 1-3 .

[0040] Table 1

[0041] The x, y, and β values ​​of the high-gloss, high-colorfastness fluorescent polyester fiber after 200 hours of aging were tested according to ASTM G155, "Nonmetallic Materials - Xenon Lamp Aging Test Method". The test results are shown in Table 2. For detailed results, please refer to... Figures 4-6 .

[0042] Table 2

[0043] Table 3

[0044] Combined with Table 2, Figures 4-6 The data, combined with the color difference results before and after aging in Table 3, are analyzed comprehensively: Before aging, the chromaticity coordinates (x, y) of Examples 1-3 and Comparative Examples 1-6 all fell within the fluorescent yellow gamut specified in EN1SO20471:2013, and the fluorescence reflectance coefficient β was higher than the standard minimum limit β. min =0.7; This proves that the initial optical properties of each group of fluorescent polyester fibers meet the high visibility clothing standard, and the addition of silica will not have a significant adverse effect on the initial fluorescence performance of the fibers.

[0045] After 200 hours of xenon lamp aging, the chromaticity coordinates and fluorescence brightness β of all samples decreased, but the weather resistance varied significantly among the samples. 1. Color coordinate stability: In Examples 1-3, the (x,y) coordinate shift was small, and the points remained within the standard fluorescent yellow range after aging. In Comparative Examples 1 and 4, the color coordinates shifted significantly, with the x value increasing and the y value decreasing, and the hue shifting significantly towards the red hue, indicating poor hue stability.

[0046] 2. Fluorescence reflectance coefficient β: After aging, the β values ​​of all samples decreased. The β value of the Example group remained above 0.94, with a high fluorescence brightness retention rate; the β values ​​of Comparative Examples 1 and 4 decreased to 0.7985 and 0.7903, respectively, after aging, which were very close to the critical threshold of 0.7, and the fluorescence brightness decayed severely.

[0047] 3. Aging color difference ΔE: The maximum total color difference ΔE before and after aging in the example was only 9.56; while the color difference ΔE of Comparative Examples 1 and 4 was as high as 34.19 and 35.73, respectively, with drastic color changes. The color difference data directly shows that the silica-modified sample had a lower degree of color change after light aging.

[0048] In summary, silica modification can effectively improve the weather resistance of fluorescent polyester fibers, inhibit photodegradation of fluorescent dyes, slow down hue shift, reduce the rate of fluorescence brightness decay, and significantly improve aging and discoloration problems. Under long-term light exposure, silica-modified examples can better maintain optical performance and continuously meet the chromaticity and fluorescence brightness requirements of EN ISO 20471:2013 for high-visibility fabrics.

[0049] This invention addresses the problems of poor color fastness and uneven gloss in existing direct melt spinning methods for preparing fluorescent polyester fibers. It provides a technical solution that constructs a composite system by adsorbing fluorescent pigments onto silica, combined with melt extrusion granulation spinning, to achieve a synergistic improvement in fiber gloss and color fastness. Polyester chips are used as the substrate, and a silica-fluorescent pigment composite is introduced as the functional component. Utilizing the high specific surface area and adsorption properties of nano-silica, the fluorescent pigment is stably loaded onto its surface and within its pores, forming uniformly dispersed composite particles and preventing pigment agglomeration. Simultaneously, the optical properties of silica enhance the fiber's reflectivity, achieving a high-gloss effect. A three-step method of "composite preparation - masterbatch preparation - melt spinning" is employed. First, a stable silica-fluorescent pigment composite is prepared through a solution adsorption process. Then, the composite is blended and granulated with polyester chips. Finally, by controlling parameters such as spinning temperature and draw ratio, the fiber forming quality is ensured, further locking in the fluorescent pigment and improving color fastness.

[0050] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the present invention.

Claims

1. A high-gloss, high-colorfastness fluorescent polyester fiber, characterized in that: The high-gloss, high-colorfastness fluorescent polyester fiber is composed of a polyester matrix and a silica-fluorescent pigment composite; the silica-fluorescent pigment composite accounts for 3% to 8% of the total fiber mass, with the remainder being the polyester matrix; in the silica-fluorescent pigment composite, the fluorescent pigment loading is 15% to 30% of the silica mass.

2. The high-gloss, high-colorfastness fluorescent polyester fiber as described in claim 1, characterized in that: The particle size of the silica is 20~100nm.

3. The high-gloss, high-colorfastness fluorescent polyester fiber as described in claim 1, characterized in that: The fluorescent pigment is selected from at least one of rare earth phosphors, fluorescent pigments, and fluorescent dyes, and the particle size of the fluorescent pigment is <5μm.

4. The high-gloss, high-colorfastness fluorescent polyester fiber as described in claim 1, characterized in that: The polyester substrate is polyethylene terephthalate (PET) or polybutylene terephthalate (PBT), with an intrinsic viscosity of 0.65~0.85 dL / g.

5. The method for preparing high-gloss, high-colorfastness fluorescent polyester fiber according to any one of claims 1 to 4, characterized in that, include, Nano-silica was mixed with fluorescent pigment and stirred in an aqueous solution at 60-80℃ for 2-4 hours for adsorption. After centrifugation and vacuum drying at 80-100℃, a silica-fluorescent pigment composite was obtained. The silica-fluorescent pigment composite was mixed with polyester chip powder and an antioxidant was added. The mixture was stirred at 400-1000 r / min for 10-20 min, and then melt-extruded, granulated, and dried to obtain the masterbatch. The obtained masterbatch is mixed with polyester chips, melted, filtered and extruded through a spinneret, then cooled, oiled, wound and stretched to obtain the fluorescent polyester fiber.

6. The preparation method according to claim 5, characterized in that: The mass ratio of the nano-silica to the fluorescent pigment is 3.3~6.7:

1.

7. The preparation method according to claim 5, characterized in that: Based on the mass percentage of the masterbatch raw materials, the contents of the silica-fluorescent pigment composite, polyester chip powder, and antioxidant are 5%~12%, 88%~95%, and 0.1%~0.3%, respectively.

8. The preparation method according to claim 5, characterized in that: The mass ratio of the masterbatch to the polyester chips is 10~20:80~90.

9. The preparation method according to claim 5, characterized in that: The masterbatch is obtained by melt extrusion granulation and drying, wherein the extrusion temperature is 230~280℃, the screw speed is 200~300r / min, the barrel temperature gradient is 230℃~250℃~260℃~280℃, the drying temperature is 80~120℃, and the drying time is 4~6h.

10. The preparation method according to claim 5, characterized in that: The fluorescent polyester fiber is obtained by extruding the melted and filtered material through a spinneret, followed by cooling, oiling, winding, and stretching. The spinneret has a spinneret orifice diameter of 0.2-0.5 mm and a number of 36-72 orifices; the oiling rate is controlled at 0.5%-0.8%; the extrusion temperature is 255-290℃; cooling is achieved by cooling the melt stream through a ring-blown air system at a speed of 0.5-1.2 m / s and a temperature of 20-25℃; the winding speed is 1500-2000 m / min; the stretching ratio is 2.5-3.2; and the setting temperature is 110-130℃.